Civic Education on Acts of Intolerance in One of the Vocational High Schools in Jayapura, Papua - Irianto, Petrus (Bina Nusantara University, 2024)
The research aimed to analyze civic education against acts of intolerance in vocational schools, with a focus on the Department of Automotive Engineering in Jayapura. Common forms of intolerance, including discrimination, harassment, and exclusion based on ethnicity, religion, race, or culture, were the primary focus. There were 45 students from class X selected as respondents through purposive sampling applying a quantitative descriptive survey method. The research instrument consisted of 18 questions covering seven categories of intolerance. The survey data were analyzed descriptively to reveal the type and frequency of intolerance experienced by students. The research results show that most students in vocational schools experience acts of intolerance, especially verbal insults and religion-based intolerance. Verbal insults often involve derogatory comments or attitudes related to religious differences, while religion-based intolerance is manifested through a lack of respect for different beliefs or practices. The research also identifies a lack of understanding and awareness of the importance of respecting differences as a key factor in driving intolerance. This problem is exacerbated by the absence of formal education on diversity and tolerance in the school curriculum. Students express the need for more educational initiatives on tolerance and diversity in schools to support equality and solidarity efforts, which can foster respect across diverse backgrounds. These efforts are expected to reduce intolerance and promote a more inclusive and unified school environment.